2020
DOI: 10.1111/bcp.14637
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐guided antiplatelet treatment versus conventional therapy: A systematic review and meta‐analysis

Abstract: This meta-analysis was carried out to explore if a personalized antiplatelet strategy based on genotyping is superior to conventional therapy.Methods: PubMed, Web of Science, EMBASE and the Cochrane Library were searched from the inception of each database to 5 May 2020. Studies reporting endpoints in genotype-guided treatment group and conventional treatment group were included. The endpoint results were presented as the risk ratio (RR), with 95% confidence interval (CI).Results: A total of 10 561 patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Our results are consistent with previous studies of clopidogrel efficacy in CYP2C19 LoF genotype carriers, although the previous evidence was predominantly from high-risk acutely hospitalized patient groups (2427), with limited follow-up periods (rarely over 12 months). Some studies reported that the effect of CYP2C19 genotype on reducing clopidogrel efficacy was limited to the short-term (1-6 months) only (28,29), but in our community based longer term follow-up we found no evidence for deviation from the proportional hazards assumptions, with survival analysis results suggesting sustained effects over the follow-up period.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with previous studies of clopidogrel efficacy in CYP2C19 LoF genotype carriers, although the previous evidence was predominantly from high-risk acutely hospitalized patient groups (2427), with limited follow-up periods (rarely over 12 months). Some studies reported that the effect of CYP2C19 genotype on reducing clopidogrel efficacy was limited to the short-term (1-6 months) only (28,29), but in our community based longer term follow-up we found no evidence for deviation from the proportional hazards assumptions, with survival analysis results suggesting sustained effects over the follow-up period.…”
Section: Discussionsupporting
confidence: 93%
“…A recent meta-analysis of 16 studies (8 RCTs and 8 cohorts) concluded that genotype-guided antiplatelet treatment (primarily based on CYP2C19 LoF alleles) improved patient outcomes for major cardiovascular events (e.g. Relative Risk for MI 0.45: 95% CI 0.35 to 0.58, p<0.00001), with decreased risk of major bleeding (27). Treatment strategy in the different metabolizer groups varied between individual studies, but included use of higher doses of clopidogrel (150 mg/d instead of the usual 75 mg/d), or prescribing of prasugrel or ticagrelor, or a combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with previous studies of clopidogrel efficacy in CYP2C19 LoF genotype carriers, although the previous evidence was predominantly from high-risk acutely hospitalised patient groups, [26][27][28][29] with limited follow-up periods (rarely over 12 months). Some studies reported that the effect of CYP2C19 genotype on reducing clopidogrel efficacy was limited to the short term (1-6 months) only, 30 31 but in our community based longer term follow-up we found no evidence for deviation from the proportional hazards assumptions, with survival analysis results suggesting sustained effects over the follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…Although multiple lines of evidence support the association between CYP2C19 LOF (*2 and *3) alleles and ischemic events in patients treated with clopidogrel, homozygous carriers of LOF alleles are at higher risk than heterozygous carriers [7,30,31]. Conclusions from recent RCTs and meta-analyses, nevertheless, have not yet reached agreement on the clinical e cacy of gene-guided antiplatelet therapy [19,29,32]. Due to the lack of su cient evidence, the current guidelines and consensus state that routine genetic testing is not recommended for tailoring DAPT [11,33,34].…”
Section: Discussionmentioning
confidence: 99%